Mass transport limitations in microchannel methanol-reforming reactors for hydrogen production. (16th October 2020) - Chen, Junjie; Li, Linke
Abstract: The potential of methanol reforming systems to greatly improve productivity in chemical reactors has been limited, due in part, to the effect of mass transfer limitations on the production of hydrogen. There is a need to determine whether or not a microchannel reforming reactor system is operated in a mass transfer-controlled regime, and provide the necessary criteria so that mass transfer limitations can be effectively eliminated in the reactor. Three-dimensional numerical simulations were carried out using computational fluid dynamics to investigate the essential characteristics of mass transport processes in a microchannel reforming reactor and to develop criteria for determining mass transfer limitations. The reactor was designed for thermochemically producing hydrogen from methanol by steam reforming. The mass transfer effects involved in the reforming process were evaluated, and the role of various design parameters was determined for the thermally integrated reactor. In order to simplify the mathematics of mass transport phenomena, use was made of dimensionless numbers or ratios of parameters that numerically describe the physical properties in the reactor without units. The results indicated that the performance of the reactor can be greatly improved by means of proper design of catalyst layer thickness and through adjusting feed composition to minimize or reduce mass transfer limitations in the reactor. There is not an effective method to reduce channel dimensions if the flow rate remains constant, or to reduce fluid velocities if the residence time is kept constant. The rate of the reforming reaction is limited by mass transfer near the entrance of the reactor and by kinetics further downstream, when the heat transfer in the autothermal system is efficient. Finally, the criteria that can be used to distinguish between different mass transport and kinetics regimes in the reactor with a first-order reforming reaction were presented. Graphical abstract: Image 1 Highlights: Catalyst layer thickness and feed composition are vital in enhancing mass transfer. It is not always effective to reduce channel dimensions and fluid velocities. The reforming reaction rate is limited by mass transfer near the entrance. The reforming reaction rate is limited by kinetics further downstream. The criteria for determining mass transfer limitations have been presented.